PENGUATAN CIVIC LITERACY BERBASIS KARAKTER, MULTIKULTURAL, DAN GREEN EDUCATION - Wahyudin Noe; Yunisca Nurmalisa; Anwar Nada (Civic Education Law and Humaniora : Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
This community service activity, in the form of a guest lecture involving students of the Civics Education Study Program at the University of Lampung, aimed to analyze the integration of Civics Education, character education, and multicultural education based on green education in supporting the achievement of the Sustainable Development Goals (SDGs). This activity employed an educational and participatory approach through material delivery and interactive discussions. The results of this activity contributed to improving participants' understanding of the concept of citizenship and environmental character values, as well as fostering multicultural awareness and environmental concern. The activity ran smoothly and successfully, as indicated by high enthusiasm from participants in listening to the material and high interaction throughout. Furthermore, this activity can contribute to the achievement of the SDGs in the areas of quality education (SDG 4), climate (SDG 13), peace (SDG 16), and partnership (SDG 17). The integration of Civics Education, character education, and multicultural education based on green education creates a holistic and transformative learning model that addresses the challenges of the times.